2012
DOI: 10.1002/ardp.201200018
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐Acting Diether Derivatives of Piperidine and Homopiperidine with Histamine H3 Receptor Antagonistic and Anticholinesterase Activity

Abstract: The study presents novel biological properties of diether derivatives of homo- or substituted piperidine ligands of the histamine H(3) receptor. The compounds were evaluated for their inhibitory potency against acetylcholinesterase (AChE) from the electric eel and butyrylcholinesterase (BuChE) from horse serum. The most interesting multifunctional compound 13 displayed high affinity for the cloned hH(3) R (K(i)  = 3.48 nM) and moderate inhibitory potency against both enzymes (IC(50) AChE = 7.91 µM and BuChE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 46 publications
3
17
0
Order By: Relevance
“…The results of docking indicate that the critical amino acids interacting with different parts of selected molecules are as follows: Glu 206 (TM5) in the interaction with basic moiety, Tyr 115 (TM3) and Tyr 374 (TM6) residues interact with linker, and Tyr 189 (TM5) and Phe 398 (TM7) forms the hydrophobic pocket with hydrophobic/aromatic moiety ( Figure S3.1). These findings are in close agreement with the findings published previously (Axe et al, 2006;Bajda et al, 2012;Harusawa et al, 2013;Kuder et al, 2016;Łażewska et al, 2016;Lepailleur et al, 2014;Levoin et al, 2013;Morini et al, 2006;Sheng et al, 2015;Wen et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…The results of docking indicate that the critical amino acids interacting with different parts of selected molecules are as follows: Glu 206 (TM5) in the interaction with basic moiety, Tyr 115 (TM3) and Tyr 374 (TM6) residues interact with linker, and Tyr 189 (TM5) and Phe 398 (TM7) forms the hydrophobic pocket with hydrophobic/aromatic moiety ( Figure S3.1). These findings are in close agreement with the findings published previously (Axe et al, 2006;Bajda et al, 2012;Harusawa et al, 2013;Kuder et al, 2016;Łażewska et al, 2016;Lepailleur et al, 2014;Levoin et al, 2013;Morini et al, 2006;Sheng et al, 2015;Wen et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…At the top 80% of the ranked database 11.4% and 23% decoys were found for the randomly selected and focused decoys, respectively. Prospective screening on this model yielded seven virtual hits that were tested in a Another bovine rhodopsin based model of H3R was published by Bajda et al [34]. In their study the binding mode of selected diether derivatives of piperidine and homopiperidine was analyzed.…”
Section: H3 Receptormentioning
confidence: 99%
“…Considering both H 3 R and ChE are involved in the regulation of the amount of ACh, dual‐active acetylcholinesterase (AChE) inhibitors and H 3 R antagonists have been developed in several groups . Previous SARs on numerous H 3 R ligands indicated that O ‐ and N ‐substituted 4‐amino‐3‐(aminomethyl)phenyl ethers possess high H 3 R binding affinity and antagonist potency, particularly as 3‐(piperidin‐1‐yl)propyl ether and with a tertiary amino methyl in position 3 ( 12 – 14 , Fig.…”
Section: Bifunctional Ligands: Combining Che Inhibitors and H3 Antagomentioning
confidence: 99%